Barcelona conference on epigenetics and cancer 2016 – beyond cancer genomes. Issue 3 (4th March 2017) - Dumbovic, Gabrijela; Biayna, Josep; Font, Berta; Buschbeck, Marcus; Forcales, Sonia-V.
ABSTRACT: The Barcelona Conference on Epigenetics and Cancer (BCEC) entitled "Beyond Cancer Genomes" took place October 13 th and 14 th 2016 in Barcelona. The 2016 BCEC was the fourth edition of a series of annual conferences coordinated by Marcus Buschbeck and subsequently organized by leading research centers in Barcelona together with BDEBATE, a joint initiative of BIOCAT and "La Caixa" Foundation. Salvador Aznar-Benitah, Eduard Batlle, and Raúl Méndez from the Institute for Research in Biomedicine in Barcelona selected the 2016 BCEC panel of speakers. As the title indicates, this year's conference expanded the epigenetic focus to include additional cancer-relevant topics, such as tumor heterogeneity and RNA regulation. Methods to develop therapeutic approaches on the basis of novel insights have been discussed in great detail. The conference has attracted 217 participants from 11 countries.